Effect of sowing time on the yield and quality parameters of sunflower (Helianthus annuus) hybrids under semiarid irrigated conditions of northern India - SHEORAN, PARVENDER; SARDANA, VIRENDER; CHAHAL, V P; SHARMA, PUSHP; SINGH, SHER (The Indian Journal of Agricultural Sciences, 2015)
To evaluate the changes in seed yield and oil quality of sunflower (Helianthus annuus L.) in response to changing environmental conditions across different planting dates and genotypic variability, a field experiment was carried out during spring 2005-2008 at PAU, Ludhiana. Planting dates affected seed yields more than any of the other characteristics measured with significant yield reduction under delayed planting conditions. An increase in oleic with decrease in linoleic acid (r = –0.993*) was observed with each progressive delay in planting time. Change in the oleic/linoleic acid ratio under different planting dates suggests a possible role of environmental factors especially temperature on the seed development processes during reproductive phase further deciding the oil quality. Total heat units accumulated during the seed maturation period had positive correlation with oleic (r = 0.697*) and negative with linoleic correlation (r = –0.578*) acid. Further investigation is needed to get deeper insight into the effects on seed oil composition of the interaction between changes in temperature regime and/or planting time under field/controlled conditions for yield maximization and better quality sunflower oil.